2016
DOI: 10.3109/08039488.2016.1146796
|View full text |Cite
|
Sign up to set email alerts
|

Predicting symptoms in major depression after inpatient treatment: the role of alexithymia

Abstract: Alexithymia has been considered to have a negative influence on the course of symptoms in various psychiatric disorders. Only a few studies of depressed patients have examined whether alexithymia predicts the outcome of therapeutic interventions or the course of symptoms in naturalistic settings. This prospective study investigated whether alexithymia is associated with depressive symptoms after a multimodal inpatient treatment. Forty-five inpatients suffering from acute major depression were examined in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…Accordingly, a difficulty in identifying feelings may, hypothetically, impinge on the ability of the individual to gain effective benefit from psychotherapy. Conversely, in a study in hospital inpatients affected by major depression, Gunther et al (29) detected a predictive role for the severity of depressive symptoms at follow-up solely for the EOT factor. Indeed, higher EOT scores at baseline correlated with more severe depressive symptoms, even once the potential influence of confounding factors, such as baseline levels of anxiety and depression had been accounted for.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Accordingly, a difficulty in identifying feelings may, hypothetically, impinge on the ability of the individual to gain effective benefit from psychotherapy. Conversely, in a study in hospital inpatients affected by major depression, Gunther et al (29) detected a predictive role for the severity of depressive symptoms at follow-up solely for the EOT factor. Indeed, higher EOT scores at baseline correlated with more severe depressive symptoms, even once the potential influence of confounding factors, such as baseline levels of anxiety and depression had been accounted for.…”
Section: Discussionmentioning
confidence: 91%
“…The authors hypothesized that this finding, at variance with other studies using different forms of psychotherapy, may be related to the possibility that CBT represents a less problematic treatment option in alexithymia patients. Gunther et al (29) carried out a prospective study to evaluate the association between pre-treatment alexithymia levels (TAS-20) and depressive symptoms at follow-up (7 weeks) following multimodal inpatient treatment. Forty-five patients admitted for acute MD who had taken part in a multimodal treatment program comprising both individual therapy and psychodynamic-interactional oriented group therapy were studied.…”
Section: Alexithymia In the Treatment Of Mood Disordersmentioning
confidence: 99%
“…It could be hypothesized that the increase in the ability of describing one's own emotions, supported by the ability to act with awareness, have an impact on the level of alexithymia, and this relationship is strongest where alexithymia is a distinctive clinical feature, such as in depression (Honkalampi, Hintikka, Saarinen, Lehtonen, & Viinam€ aki, 2000). Furthermore, alexithymia is a predictor of the level of depressive symptoms after psychotherapy (G€ unther, Rufer, Kersting, & Suslow, 2016). Mindfulness, and in particular the ability to describe, might be an important strategy to improve an important clinical aspect that contributes to perpetuate the depressive symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…Alexithymia has been recognized as associated with several somatic illnesses and mental disorders [ 21 ]. Furthemore studies detected that the presence of alexithymia has a negative influence on the course of symptoms in psychiatric disorders [ 22 ]. In particular some authors have suggested that alexithymia could be considered a vulnerability factor in the development of psychiatric disorders such as depression [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%